2019
DOI: 10.1186/s12877-019-1093-3
|View full text |Cite
|
Sign up to set email alerts
|

Objective physical measures and their association with subjective functional limitations in a representative study population of older Thais

Abstract: Background In this study, we analyzed elderly people in Thailand to identify the validity of suggested cutoff points of physical measures, handgrip strength, usual walking speed, and a composite score of both measures to predict functional limitations. Moreover, we examined whether these physical performance measures are accurate indicators of the investigated health outcomes. Methods Using Receiver Operating Characteristics (ROC) analysis, we investigated a sample of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 40 publications
(40 reference statements)
1
13
0
1
Order By: Relevance
“…Three studies also reported the prevalence of IADL disability by gender, with a higher prevalence reported among females (65.4%) compared to males (36.9%, p<0.01). (14,27,33) The prevalence of IADL disability was relatively similar among community dwelling participants (49.6%) and older adults recruited from outpatient/primary care setting (55.5%). As only one study recruited institutionalised older adults and reported data on IADL, this information was not pooled in our analysis.…”
Section: Iadl Disabilitymentioning
confidence: 96%
See 2 more Smart Citations
“…Three studies also reported the prevalence of IADL disability by gender, with a higher prevalence reported among females (65.4%) compared to males (36.9%, p<0.01). (14,27,33) The prevalence of IADL disability was relatively similar among community dwelling participants (49.6%) and older adults recruited from outpatient/primary care setting (55.5%). As only one study recruited institutionalised older adults and reported data on IADL, this information was not pooled in our analysis.…”
Section: Iadl Disabilitymentioning
confidence: 96%
“…The prevalence of cognitive impairment was reported to be higher for female than male participants regardless of age group (60-69 years or 70-79 years) (33) and in frail individuals compared to robust individuals. ( 30)…”
Section: Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with earlier studies (Schwert et al, 2017;Srisurapanont et al, 2017), we found no significant correlations between objective cognitive measures and perceived forgetfulness (r −.08 to −.18). Objective measures for physical performance showed strong associations with perceived physical function (rs −0.49 to 0.46, ps < 0.001), while other studies have reported moderate relationships (Ostir et al, 2001;Prasitsiriphon & Weber, 2019).…”
Section: Discussionmentioning
confidence: 77%
“…Alternatively, moderate associations have been found between objective measures of physical health and self-reported health (Ostir et al, 2001;Prasitsiriphon & Weber, 2019). Further, physical performance was related to perceptions about competency regarding activities of daily living (ADLs; Cress et al, 1995).…”
mentioning
confidence: 99%